Inheritance of resistance to leaf rust In four bread wheats - and J.B. SHARMA, P BAHADUR, RAM CHARAN (Indian Phytopathology, 2002)
Resistance to an array of pathotypes and inheritance of resistance to three selected pathotypes viz., 106 (OR9), 104B (29R23) and 77-5 (121R63-1) of Puccinia recondita f.sp. tritici was studied in three popular bread wheat cultivars HD2189, HD2285 and Vaishali, and a widely used genetic stock HD2160. Among the four wheats, Vaishali was found resistant to all the pathotypes of leaf rust while others showed differential reactions. Inheritance studies revealed the presence of one dominant and one recessive gene in HD2160, two dominant independent resistant genes in HD2285, and three dominant independent resistance genes each in HD2189 and Vaishali against pathotype 106 (OR9). The resistance genes identified in HD2160 and HD2285 were ineffective to pathotype 1048 (29R23) and 77-5 (121R63-1). Out of the three resistance genes identified in HD2189, only one showed resistance to pathotype 1048 (29R23) but none of these was effective to 77-5 (121R63-1). Among the three resistance genes in Vaishali one was also effective against pathotypes 1048 (29R23) and 77-5 (121R63-1). F2 analysis of crosses of Vaishali with HD2160 and HD2285 to pathotypes 1048 (29r23) and 77-5 (121R63-1) also showed operation of one gene for resistance from Vaishali. Monogenic segregation in crosses involving HD2189 with HD2160 and HD2285, where resistance was derived from HD2189, was non-allelic with resistance gene in Vaishali when tested with pathotype 1048 (29R23). Absence of susceptible segregants in F 2's of all intercrosses of resistant parents to pathotype 106 (OR9)indicated the presence of at least one common resistance gene in all the wheats. Genes Lr23 in HD 2160, HD 2285; Lr14a in HD 2285 and Lr24 in Vaishali were confirmed by test of allelism.